Linguistic Analysis of Albanian Advertising Slogans: Effectiveness and Rhetorical Strategies - Agarwal, Priyanka (Journal of Research in Vocational Education, 2026)
This paper provides an overview of the definition of advertising slogans, noting the lack of a uniform definition in academic literature. It also analyzes the language of advertising from a linguistic perspective, identifying the linguistic devices employed in advertising texts. The study examines a corpus of 85 Albanian advertising slogans, which were categorized based on the language and rhetorical devices utilized. The analysis identifies the most and least frequently used figurative language, sound techniques, and rhetorical devices in the slogans. Additionally, the study explores the relationship between the stylistic features of the slogans and their perceived effectiveness in conveying the brand's message to the target audience (Abdi & Irandoust, 2013).